2012
DOI: 10.1038/onc.2012.387
|View full text |Cite
|
Sign up to set email alerts
|

Increased replication initiation and conflicts with transcription underlie Cyclin E-induced replication stress

Abstract: It has become increasingly clear that oncogenes not only provide aberrant growth signals to cells but also cause DNA damage at replication forks (replication stress), which activate the ataxia telangiectasia mutated (ATM)/p53-dependent tumor barrier. Here we studied underlying mechanisms of oncogene-induced replication stress in cells overexpressing the oncogene Cyclin E. Cyclin E overexpression is associated with increased firing of replication origins, impaired replication fork progression and DNA damage tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
238
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(254 citation statements)
references
References 51 publications
11
238
1
4
Order By: Relevance
“…S6B,C). The latter two features closely resemble the effects of oncogene activation (Neelsen et al 2013) and thus most likely reflect the licensing defects common to these genetic conditions (Hook et al 2007;Blow and Gillespie 2008) and their consequences in terms of nucleotide depletion (Bester et al 2011) and/or interference with transcription (Jones et al 2013). Although ssDNA sensors (e.g., RPA chromatin loading and PCNA ubiquitylation) ( Fig.…”
Section: Deregulation Of Origin Licensing Induces Ssdna Gaps On Replimentioning
confidence: 99%
“…S6B,C). The latter two features closely resemble the effects of oncogene activation (Neelsen et al 2013) and thus most likely reflect the licensing defects common to these genetic conditions (Hook et al 2007;Blow and Gillespie 2008) and their consequences in terms of nucleotide depletion (Bester et al 2011) and/or interference with transcription (Jones et al 2013). Although ssDNA sensors (e.g., RPA chromatin loading and PCNA ubiquitylation) ( Fig.…”
Section: Deregulation Of Origin Licensing Induces Ssdna Gaps On Replimentioning
confidence: 99%
“…In early stages of cancer development, oncogene activation leads to replication stress [1][2][3][4] . Mechanisms by which oncogenes can induce replication stress include insufficient nucleotide pools to support extensive replication 4,5 , lack of other replication factors 6 and collision between replication and transcription 7 . In addition, a recent study showed that loss of FHIT expression encoded by the fragile histidine triad gene located in the fragile site locus FRA3B can initiate replication stress and continue genomic instability 8 .…”
mentioning
confidence: 99%
“…The mutation of MCM4 or MCM2 reduces the activity of the MCM complex, limiting the amount of available back-up origins, which results in increased RS, genomic instability and a cancer-prone phenotype [14][15][16]. In contrast, the overexpression of certain oncogenes (Myc, Ras…) has the opposite effect and increases the firing of origins of replication, leading to a depletion of the cellular pool of nucleotides (dNTPs) [17][18][19][20][21]. The reduced level of dNTPs slows down the progression of the forks and increases the chance of fork stalling per se.…”
Section: Sources Of Replication Stress During Transformationmentioning
confidence: 99%
“…Moreover, overexpression of RNR, rather than its loss, is frequently found in human cancers [22]. Regardless of the mechanism, supplementation with nucleosides has been shown to limit oncogene-induced RS in vitro, Besides any effect on the nucleotide pool, the higher number of active origins generates more replication-transcription collisions that lead to stalled replication forks [18], expression of common fragile sites and genome instability [24]. There is increasing evidence showing that the formation of RNA-DNA hybrid called R-loops is central to the replicationtranscription collisions [25].…”
Section: Sources Of Replication Stress During Transformationmentioning
confidence: 99%